2016
DOI: 10.3390/e18020053
|View full text |Cite
|
Sign up to set email alerts
|

Bounding Extremal Degrees of Edge-Independent Random Graphs Using Relative Entropy

Abstract: Edge-independent random graphs are a model of random graphs in which each potential edge appears independently with an individual probability. Based on the relative entropy method, we determine the upper and lower bounds for the extremal vertex degrees using the edge probability matrix and its largest eigenvalue. Moreover, an application to random graphs with given expected degree sequences is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Let G be a random graph on n vertices, where uv is an edge with probability p uv and each edge is independent of each other edge. It is shown that [30,39]…”
Section: Algorithmmentioning
confidence: 99%
“…Let G be a random graph on n vertices, where uv is an edge with probability p uv and each edge is independent of each other edge. It is shown that [30,39]…”
Section: Algorithmmentioning
confidence: 99%
“…Information theory, relative entropy, and the Kullback-Leibler divergence are now widely used concepts (see, e.g., References [1][2][3]). Entropy-based algorithms have enabled engineers and researchers to measure the uncertainty and irregularity of complex systems and data [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible, however, to construct an argument as to why the two quantities might be in such strong correlation. A number of approaches have been made to obtain upper and lower bounds for entropy measures in random and more general graphs [6,22] and in the analysis that follows, we will make use of a bounding approach to identify how the correlation between vertex entropy and chromatic information may arise.…”
Section: Theoretical Discussion Of the Resultsmentioning
confidence: 99%